2010
DOI: 10.1007/s00445-010-0377-4
|View full text |Cite
|
Sign up to set email alerts
|

Volcano collapse promoted by progressive strength reduction: new data from Mount St. Helens

Abstract: Rock shear strength plays a fundamental role in volcano flank collapse, yet pertinent data from modern collapse surfaces are rare. Using samples collected from the inferred failure surface of the massive 1980 collapse of Mount St. Helens (MSH), we determined rock shear strength via laboratory tests designed to mimic conditions in the pre-collapse edifice. We observed that the 1980 failure shear surfaces formed primarily in pervasively shattered older dome rocks; failure was not localized in sloping volcanic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Saturated unit weights ( γ sat ), which were used in slope stability assessments, are defined by the following: γsat=()()ρwg()ρrρw+()()ρwg()ϕ1ϕS1+()ϕ1ϕ where ρ r is the density of the rock (either unaltered or altered) and S is the volumetric saturation ( S = 1 for saturated rocks). In our simulations, saturated unit weights are 23 kN/m 3 for unaltered rocks and 16 kN/m 3 for altered rocks (Table ), consistent with previous studies (Reid et al, ; Watters & Delahaut, ).…”
Section: Modeling Methods and Input Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…Saturated unit weights ( γ sat ), which were used in slope stability assessments, are defined by the following: γsat=()()ρwg()ρrρw+()()ρwg()ϕ1ϕS1+()ϕ1ϕ where ρ r is the density of the rock (either unaltered or altered) and S is the volumetric saturation ( S = 1 for saturated rocks). In our simulations, saturated unit weights are 23 kN/m 3 for unaltered rocks and 16 kN/m 3 for altered rocks (Table ), consistent with previous studies (Reid et al, ; Watters & Delahaut, ).…”
Section: Modeling Methods and Input Parameterssupporting
confidence: 91%
“…Triaxial testing of igneous rocks produces cohesion ( c ) of up to 10,000 kPa, but the cohesion of highly altered rocks can be as low as 10 kPa (del Potro & Hürlimann, ; Reid et al, , ; Watters & Delahaut, ; Watters et al, ) (Figure b). Fractured but unaltered Mount St. Helens dacite yields internal friction angle ( φ ) values of 27° to 35° (Reid et al, ; Figure c), whereas other studies report internal friction angles of around 35° for unaltered volcanic rock (Apuani et al, ; Moon et al, ; Pola et al, ; Reid et al, ; Watters et al, ) and as low as 13° for altered rock (del Potro & Hürlimann, ; Mielke et al, ; Watters et al, ; Wyering et al, ). We simulate altered layers with a constant cohesion ( c ) of 200 kPa and internal friction angle ( φ ) of 20° (Figures b and c, Table ) to represent reduced mechanical strength due to argillic alteration processes.…”
Section: Modeling Methods and Input Parametersmentioning
confidence: 99%
“…We had three objectives: 1) to provide deeper resistivity information requested by other scientists who have conducted high-frequency airborne EM surveys; we also wanted to bridge the gap to lowerfrequency MT measurements (Finn et al, 2001(Finn et al, , 2007Hill et al, 2009); 2) to map where the ground water lies in and near the volcano (Ingebritsen et al, 2006), and 3) to image hot rock from the 2004 to 08 dome eruption (Sherrod et al, 2008). In the context of recent indications that the volcano is repressurizing (Battaglia et al, 2014), we hope that these new data will assist decision-tree exercises to predict future eruptive behavior in this and other volcanoes, including the potential for volcanic edifice collapse (Reid, 2004;Reid et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Reid (2004) suggested that ground water may play a significant role in volcanic edifice collapse events (Schmincke, 1998;Ingebritsen et al, 2006;Reid et al, 2010). Wells on volcanoes are not easily drilled, nor easily permitted.…”
Section: Where Is the Water?mentioning
confidence: 99%
“…Compare to the traditional limit equilibrium methods, the obvious advantages of the finite element method are as follows [6][7][8][9][10][11][12] :…”
Section: Introductionmentioning
confidence: 99%